Programming of skilled football players training process in the second cycle of specially created training during the year - V.M. Kostiukevich; V.A. Stasiuk; N.Yu. Shchepotina; A.A. Dyachenko (Physical Education of Students, 2017)
The purpose of the research is to prove experimentally the skilled football players training process in the annual macrocycle on the basis of programming. Material and methods: the skilled football players participated in a research (n=20, age 18-23 years). Control provided use of the following tests: 30 m run; shuttle run 7х50 m; long jump from the spot; Cooper's test. Results: programs of training microcycles were developed. In each program such components of the training were considered: value and orientation of loads; means (non-specific and specific); modes of coordination complexity of exercises performance; training time; time for renewal of competition form, theoretical and psychological preparation; load coefficient value; intensity of training load coefficient. Conclusions. Programming of training process has to be carried out on the basis of systemically structural approach: the development of programs of less structural formations has to be subordinated to the main structural formations. The structure of microcycles includes programs of trainings. Programs of stages consist of a series of training microcycles programs. The program of a training cycle unites all structural formations.